Distribution of heavy metals and radionuclides in the sediments and their environmental impacts in Nansha Sea area, South China Sea. (May 2021) - Liu, Jing; Peng, Anguo; Deng, Shuang; Liu, Min; Liu, Guangshan; Li, Chao
Abstract: Activity concentrations of radionuclides ( 238 U, 226 Ra, 232 Th, and 40 K) in the sediments of eight sampling stations and heavy metal concentrations (Cr, Co, Ni, Cu, Zn, As, Cd, and Pb) in the sediments of two long cores from Nansha Sea area were obtained by high-purity germanium spectroscopy and inductively coupled plasma atomic emission spectrometry. In a correlation analysis between the radionuclides and heavy metals, 232 Th was positively correlated with As and Pb. 238 U demonstrated a significant positive correlation with Co, Ni, Cu, Zn, and Cd. 40 K was positively correlated with Co, Ni, and Cu. The geo-accumulation index, pollution load index, potential ecological risk index, and multivariate statistical techniques were used to evaluate the pollution degree and possible sources of heavy metals in the sediments. An ecological risk assessment suggested that Cr, Co, Ni, Cu, Zn, Cd, and Pb were primarily derived from natural processes, while the source of As may be related to natural processes and human activities. Graphical abstract: The geo-accumulation index (Igeo ) of heavy metals in the sediment profiles was used to study the quantitative index of heavy metal pollution in sediments. Unlabelled Image Highlights: A total of 121 samples from two long sediment cores with depths of 773 cm and 420 cm were analyzed. Four radionuclides and eight heavy metals in sediments were studied at the same time. 232 Th was positively correlated with Pb. 238 U showed significant positive correlation with Co, Ni, Cu, Zn and Cd. The high concentration of As in the core was related to the environment and climate change of the Last Glacial Period.